The Problem of Gene Patents - Nuno Pires de Carvalho (Washington University Global Studies Law Review, 2004)
This Article submits that the main problem with gene patents is the failure to meet the condition of alternativeness of inventions-a condition that embodies a core function of the patent system. As a result, gene patents conflict with the very rationale of the patent system.
Keywords: Biotechnology; Human genetics; Patent law; European Union; United States